2009
DOI: 10.1002/pros.21045
|View full text |Cite
|
Sign up to set email alerts
|

PTEN‐mediated G1 cell‐cycle arrest in LNCaP prostate cancer cells is associated with altered expression of cell‐cycle regulators

Abstract: The results indicate that PTEN dependent gene expression is important in cell-cycle regulation and is mediated by both Akt-dependent and -independent mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…The normalized PTEN DNA copy number change on chromosome 10 corresponding to the PTEN gene is consistent with the known PTEN status in these cell lines: null in PC3 and reduced in heterozygous LNCaP cells but 2 copies in VCaP cells [4345] (Fig 4H). Based on our CNV cutoff (Z score > 3 for amplification, or < -3 for loss), 1/8 LNCaP, 6/7 PC3, and 0/5 VCaP cells were called as PTEN loss.…”
Section: Resultssupporting
confidence: 77%
“…The normalized PTEN DNA copy number change on chromosome 10 corresponding to the PTEN gene is consistent with the known PTEN status in these cell lines: null in PC3 and reduced in heterozygous LNCaP cells but 2 copies in VCaP cells [4345] (Fig 4H). Based on our CNV cutoff (Z score > 3 for amplification, or < -3 for loss), 1/8 LNCaP, 6/7 PC3, and 0/5 VCaP cells were called as PTEN loss.…”
Section: Resultssupporting
confidence: 77%
“…However, our data here showed that the high expression of hepaCAM caused a G1 accumulation. Such a phenomenon has also been observed in other tumor suppressors such as PTEN, which arrested prostatic cancer cell cycle at G1 phase [Van Duijn et al, 2010], arrested melanoma at G2 phase [Jacob et al, 2009] and had no effect on the cell cycle of leukemia [Seminario et al, 2003]. These data suggested that hepaCAM may inhibit the proliferation of different cancer through different approaches.…”
Section: Discussionmentioning
confidence: 77%
“…Increasing evidence supports anti-tumor roles for FOXO members in CaP. For instance, the loss of FOXO3a promotes cancer formation in the TRAMP CaP mouse model [24], whereas the upregulation or activation of FOXO proteins leads to growth arrest and apoptosis in CaP cells [2527]. In contrast, Akt directly phosphorylates FOXO family members, thereby antagonizing the functions of FOXOs by promoting their association with 14-3-3 proteins and thus preventing their nuclear translocation [28].…”
Section: Discussionmentioning
confidence: 99%